Introduction to the Special Issue on “Engineering and Applications of Software Agents” (Informatica, 2016)
The aim of this Special Issue is to introduce to the readers a selection of papers from the 3rd  Workshop on Applications of Software Agents – WASA 2013 in the area of agent-based modelling and simulation. WASA’2013 was held in Sinaia, Romania, during October 11-13, 2013. The WASA 2013 workshop was organized within the framework of the 17th International Conference on System Theory, Control and Computing –ICSTCC’2013. The aim of the WASA series of workshops is to contribute to the advancement of technologies and applications of software agents' by bridging the gap between the theory and practice of software agents.